Evaluating the Impact of Presence of Organic Matter on Environmental Samples and Sample Processing Technique on RNA Detection of PEDV - C. Grace Elijah; Allison K. Blomme; Olivia L. Harrison; Jianfa Bai; Jason C. Woodworth; Cassandra K. Jones; Elizabeth G. Poulsen-Porter; Chad B. Paulk; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
Environmental sampling has become a commonly accepted diagnostic sampling technique for a means of identifying breaks in biosecurity. However, environmental samples have yet to be validated for reverse transcriptase real-time PCR (qRT-PCR) analysis and there is no standardization for environmental sample processing. Therefore, the objective of this project was to evaluate different types of environmental samples, and whether processing the samples prior to qRT-PCR analysis would impact results. Steel coupons were inoculated with PEDV in different types of environmental conditions, then were environmentally swabbed using cotton gauze. Treatments were arranged as a 5 × 4 factorial with five treatments for the different types of contamination and four treatments for the types of sample processing. Samples were processed in four different ways: no pre-qRT-PCR processing, centrifuging, syringe filtering, and centrifuging then syringe filtering to determine if pre-sample processing impacted the cycle threshold (Ct) value. Once samples were processed, they were submitted for PEDV qRT-PCR analysis. Results were reported as proportion of qRT-PCR positive and the resulting Ct value. If samples had no detectable RNA, they were assigned a Ct value of 45. For the Ct values, there was an inoculated surface × sample processing (P<0.0001) interaction indicating that the type of environmental sample and the way the sample was processed impacted the Ct value of the sample. For pure virus and virus with PBS, there was no difference in Ct values between different sample processing techniques (PP<0.05). For virus and fecal contamination, samples that were not processed or samples that were processed with centrifuging only had greater amounts of PEDV RNA detected compared to syringe filtered samples or centrifuged and syringe filtered samples (P<0.05). For virus and organic matter contamination, samples that were centrifuged had greater amounts of PEDV RNA detected compared to all other sample processing techniques (P<0.05). Main effects of inoculated surface (P<0.0001) and sample processing (P<0.0001) were also significant. For surface inoculation type, pure virus inoculation and virus with PBS inoculation had greater amounts of PEDV RNA compared to virus with feces inoculation or virus with organic matter inoculation, while virus with dirt was intermediate. For sample processing type, centrifuged samples had the greatest amount of PEDV RNA compared to syringe filtered and centrifuged then syringe filtered samples with unprocessed samples being intermediate. In summary, if environmental samples are particularly dirty, processing prior to qRT-PCR analysis will impact the results.
Keywords: Environmental samples; PCR analysis; PEDV; sample processing